An example of analyses of the echo obtained by a radio echo sounder near the Shirase Glacier, East Antarctica, using an original radar equation (extended abstract) - Izumi, Tatsuji; Nishitsuji, Akira; Wada, Makoto; Mae, Shinji (1982)
P(論文) departmental bulletin paper